Improving Students’ Reading Comprehension Using Paired Reading Method - Nihta V.F. Liando; Claudya Wati Katiandagho; Rinny Rorimpandey (Universitas Batanghari Jambi, 2023)
This study was conducted in the purpose to find out whether the implementation of paired reading can improve students’ reading comprehension at SMP SATAP N.1 Beo Selatan or not. This research was delimited on the use of paired reading in teaching reading to students at SMP SATAP N.1 Beo Selatan, especially eighth grade students. More specifically, narrative texts were selected as the reading text taught during this research. The design is pre-experimental design with one group pre-test and post-test. Class 8A was one of the classes in the eighth grade of SMP SATAP N.1 Beo Selatan, the academic year of 2020-2021 who were the subjects of this research. The class A consisted of 30 students in all. In this research, the researcher used test of narrative text which consisted of 20 questions in form of objective test in form of multiple choice as the instrument to get the data. The data analysis proves that (1) the mean score of the post-test is 7.93 and the the mean score of pre-test is 6.63, and (2) the standard deviation of the pre-test data is 0.59 whereas the post-test data is 0.95. These results of data analysis confirm that the students’ reading comprehension improves after applying paired reading as the treatment. It shows that the use of paired reading is successful in improving the students’ reading comprehension. Since paired reading is effective to be used in improving students’ reading comprehension, English teachers are suggested to implement paired reading as a useful alternative for improving students’ reading comprehension particularly narrative texts.